2019
DOI: 10.1002/job.2405
|View full text |Cite
|
Sign up to set email alerts
|

So far, so good: Up to now, the challenge–hindrance framework describes a practical and accurate distinction

Abstract: Summary There are many ways to categorize work‐related stressors, and in recent years, a common distinction in occupational health psychology is between stressors viewed as challenges versus hindrances. Is this a useful conceptualization that provides practical and theoretical implications for IO psychologists? As Kurt Lewin famously prescribed, “there is nothing so practical as a good theory,” and we discuss the challenge–hindrance framework as a developing theory that can be useful for researchers and practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
98
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(147 citation statements)
references
References 54 publications
12
98
0
1
Order By: Relevance
“…By doing so, we advance the literature by suggesting how cognitive appraisals influence employee well-being and revealing the boundary conditions of the job characteristics-employee well-being relationship. While some studies have examined the mediating role of appraisals (e.g., Boswell et al, 2004;Liu & Li, 2018), relatively less attention has been paid to the moderating role of appraisals in the job characteristics literature (O'Brien & Beehr, 2019). Our study addressed this limitation and showed that challenge appraisals moderate the associations between time urgency, role conflict, and emotional demands and work engagement, which resonates with the findings of a recent study (Li et al, 2020).…”
Section: Theoretical Implicationssupporting
confidence: 85%
See 1 more Smart Citation
“…By doing so, we advance the literature by suggesting how cognitive appraisals influence employee well-being and revealing the boundary conditions of the job characteristics-employee well-being relationship. While some studies have examined the mediating role of appraisals (e.g., Boswell et al, 2004;Liu & Li, 2018), relatively less attention has been paid to the moderating role of appraisals in the job characteristics literature (O'Brien & Beehr, 2019). Our study addressed this limitation and showed that challenge appraisals moderate the associations between time urgency, role conflict, and emotional demands and work engagement, which resonates with the findings of a recent study (Li et al, 2020).…”
Section: Theoretical Implicationssupporting
confidence: 85%
“…Framework, see Mazzola & Disselhorst, 2019); and empirical studies also showed that time pressure is negatively related to work engagement (e.g., Baethge et al, 2019;Gabriel et al, 2019;Kronenwett & Rigotti 2019). This suggests that the challenge-hindrance stressor model may not be as effective in all contexts as some researchers suggested (e.g., O'Brien & Beehr, 2019). Instead of using such an a priori categorization method, our study drew upon appraisal theory (Lazarus & Folkman, 1984) and tested empirically whether job characteristics (i.e.,…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Workload, time urgency, job responsibility, and job complexity were considered challenge stressors, whereas red tape, role ambiguity, role conflict, and hassles were labeled as hindrance stressors (Rodell and Judge, 2009). Given how meaningful and useful these categorizations are in the workplace, stress researchers have devoted great effort to probe their outcomes, so as to effectively cope with challenge and hindrance stressors in the workplace (O'Brien and Beehr, 2019). From different perspectives, such as a psychology lens (Rodell and Judge, 2009), attitude lens (LePine et al, 2005;Wallace et al, 2009;Yao et al, 2015), and behavior lens (Rodell and Judge, 2009), previous studies investigated the possible outcomes of challenge and hindrance stressors.…”
Section: Introductionmentioning
confidence: 99%
“…11 Challenge stressors refer to some stressors which are related to positive work outcomes, while hindrance stressors refer to some stressors which are related to negative work outcomes. 11,12 Based on the challenge-hindrance stressors framework, many studies have been conducted to confirm the different effects of challenge and hindrance stressors on employees' work attitudes (such as engagement or turnover intentions), 13,14,17 employees' work performance (such as creativity), 14,15 employees' work behaviors (such as counterproductive behaviors or organizational citizenship behaviors), 16,17 and so on. Among the work on this stream of studies, scholars pay more focus on the effects of challenge and hindrance stressors on common employees, rather than on supervisors who play a supervisory role.…”
Section: Introductionmentioning
confidence: 99%